Model to Determine the Cost‐Effectiveness of Screening Psoriasis Patients for Psoriatic Arthritis. Issue 2 (1st February 2021) - Iragorri, Nicolas; Hazlewood, Glen; Manns, Braden; Bojke, Laura; Spackman, Eldon
Abstract : Objective: Screening psoriasis patients for psoriatic arthritis (PsA) is intended to identify patients at earlier stages of the disease. Early treatment is expected to slow disease progression and delay the need for biologic therapy. Our objective was to determine the cost‐effectiveness of screening for PsA in patients with psoriasis in Canada. Methods: A Markov model was built to estimate the costs and quality‐adjusted life years (QALYs) of screening tools for PsA in psoriasis patients. The screening tools included the Toronto Psoriatic Arthritis Screen, Psoriasis Epidemiology Screening Tool, Psoriatic Arthritis Screening and Evaluation, and Early Psoriatic Arthritis Screening Questionnaire (EARP) questionnaires. States of health were defined by disability levels as measured by the Health Assessment Questionnaire. State transitions were modeled based on annual disease progression. Incremental cost‐effectiveness ratios and incremental net monetary benefits were estimated. Sensitivity analyses were undertaken to account for parameter uncertainty and to test model assumptions. Results: Screening was cost‐effective compared to no screening. The EARP tool had the lowest total cost ($2, 000 per patient per year saved compared to no screening) and the highest total QALYs (additional 0.18 per patient compared to no screening). The results were most sensitive to test accuracy and the efficacy of disease‐modifying antirheumatic drugs (DMARDs). No screening was cost‐effective (at $50, 000 per QALY) relative to screening when DMARDs failed to slow disease progression. Conclusion: If early therapy with DMARDs delays biologic treatment, implementing screening in patients with psoriasis in Canada is expected to represent a cost savings of $220 million per year and improve the quality of life.